Virtual Bullet Examination: Forensic Insights from CT Imaging in Gunshot Victims - Dominic Gascho (Forensic Sciences, 2025)
The decision to remove a bullet from a gunshot victim depends on its location and associated medical risks, with surgical extraction often not indicated. Radiological imaging plays a vital role in assessing gunshot wounds and locating bullets, and it is essential in both clinical and forensic contexts. This narrative review examines the use of computed tomography (CT) for virtual bullet analysis, providing insights into shape, design, fragmentation, and material composition. Traditional 2D X-ray imaging, though commonly used, has limitations in accurately assessing caliber and position due to magnification and its 2D nature. In contrast, CT scans generate 3D reconstructions for detailed and precise examination, overcoming challenges such as metal artifacts with techniques such as extended Hounsfield unit (HU) reconstructions. These methods enhance the visualization of metal objects, allowing for better analyses of lodged bullets. Dual-energy CT further differentiates materials, such as lead and copper, using HU value differences at two energy levels. These advancements enable the virtual classification, shape analysis, and material identification of bullets in forensic investigations, even when the bullet remains in the body. As CT technology progresses, its forensic applications are expected to improve, providing more accurate and comprehensive differentiations of bullet types in future cases.